Population dynamics of the non-native plant species, Coreopsis lanceolata L., at three plant community types over a three-year period following the cessation of grassland management in central Japan - Saito, Tatsuya I.; Okubo, Kumiko (Journal of Weed Science and Technology, 2025)
To characterize the population dynamics of the invasive non-native plant, Coreopsis lanceolata L., we monitored the dynamics of the populations and the invaded communities for three years after the cessation of vegetation management. The monitoring was conducted in the three community types that differ in the abundance of C. lanceolata and species composition: the Zoysia japonica Steud. dominant type (Zj), the C. lanceolata dominant type (Cl), and the Miscanthus sinensis Anderss. dominant type (Ms). The above-ground shoots of C. lanceolata were used for the monitoring. At the beginning of the survey, the number of above-ground shoots was high in the order of Cl, Zj, and Ms. The number of shoots decreased for the three years in all the community types. The degree of decrease was more conspicuous in Cl than in Zj, and the population vanished in Ms for the study period. The small shoots were more likely to die than the larger ones, particularly many small shoots died in Cl in the latter half of the study period. Most of the bolting shoots died until the next year, indicating that bolting is an important factor in the death of large shoots. The annual growth of the above-ground shoots was often negative in Cl, but not in Zj. The height of M. sinensis and woody plants tended to be high in the order of Zl, Cl, and Ms, became higher annually, and were superior to that of C. lanceolata. Their larger plants are likely to suppress the C. lanceolata populations competitively. This study showed that the C. lanceolata population could decline after the management termination, but its degree varies with the invaded community types.